2022
DOI: 10.1111/head.14289
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world assessment of the relationship between migraine‐related disability and healthcare costs in the United States

Abstract: Objective The objective of this study was to determine the associations among migraine disability assessment scores, healthcare resource utilization (HCRU; medical visits and pharmacy use) and direct medical costs among people with episodic migraine in a real‐world setting. Background Migraine is a public health concern associated with a substantial economic burden in the United States. However, the association between migraine disability and direct medical costs among people with migraine is unknown. Method T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…It should also be noted that more than 78% of patients who come to work with a headache use only half of their time at work to perform tasks effectively and nearly 25% make mistakes. This constitutes a significantly higher rate of presenteeism compared to other countries, where it averages 35%-43% [ 20 , 24 , 35 , 37 ]. Apart from loss off productivity costs, migraine is also related to a direct economic burden for migraine patients.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be noted that more than 78% of patients who come to work with a headache use only half of their time at work to perform tasks effectively and nearly 25% make mistakes. This constitutes a significantly higher rate of presenteeism compared to other countries, where it averages 35%-43% [ 20 , 24 , 35 , 37 ]. Apart from loss off productivity costs, migraine is also related to a direct economic burden for migraine patients.…”
Section: Discussionmentioning
confidence: 99%
“…Während der Großteil der Patienten eine niedrige Attackenfrequenz und niedrige Belastung zeigt, sind 10-20 % der Patienten mit hoher Attackenfrequenz für die hohe Beeinträchtigung und die Belastung des Gesundheitssystems verantwortlich [3]. Patienten mit cM zeigen demzufolge die umfangreichsten Einschränkungen der Alltagsfunktion, lange Zeiten der Arbeitsunfähigkeit und höhere gesundheitsbezogene Kosten [4].…”
Section: Empfehlungunclassified
“…Migraine is classified as a form of primary headache (3) which affects one in six adults over a 3-month period (4). According to the Global Burden of Disease, migraine is ranked second in the causes of disability (5,6), which is associated with substantial healthcare resource utilization and costs (7). Migraine is an important reason for absenteeism at work or school (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Disability can be evaluated using questionnaires and are beneficial in research and clinical settings (20,28). One study revealed the relationship between headache-related disability and healthcare costs (7). Therefore, detailed measurement of disability is important and could be effective in reducing healthcare costs.…”
Section: Introductionmentioning
confidence: 99%